2014
DOI: 10.1016/j.anai.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological characteristics of asthma in the elderly: a comprehensive study

Abstract: Based on spirometric, computed tomographic, and impulse oscillation analyses, elderly patients with asthma have greater involvement of small and large airways than nonelderly patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 55 publications
3
37
1
2
Order By: Relevance
“…A comprehensive study of elderly patients with asthma in Japan demonstrated that half of the elderly patients had non‐atopic asthma, and total serum IgE levels were significantly lower than in nonelderly patients with asthma. There were no significant differences in FeNO and blood eosinophil rate, which is a finding similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…A comprehensive study of elderly patients with asthma in Japan demonstrated that half of the elderly patients had non‐atopic asthma, and total serum IgE levels were significantly lower than in nonelderly patients with asthma. There were no significant differences in FeNO and blood eosinophil rate, which is a finding similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study using IOS found that elderly patients with asthma showed higher R5, Fres, and ALX, lower R5-R20, and more negative X5 than nonelderly patients (35). Although, in those reports, R5-R20 and Xrs parameters were implicated to reflect the small airway function, it should be implicated as the overall airway including central elements.…”
Section: Asthmamentioning
confidence: 99%
“…More recent data suggest that older patients have increased "small airway" involvement, increased neutrophilic inflammation, and decreased eosinophil function and specific antibody response compared with younger cohorts (9)(10)(11). These important, but understudied age-related changes in pulmonary function, bronchial hyperresponsiveness, host defense, and inflammation highlight the need for more investigation into this important group of patients.…”
mentioning
confidence: 99%